POS0130 INFLAMMATORY ACTIVITY IS ASSOCIATED WITH COGNITIVE IMPAIRMENT IN PATIENTS WITH RHEUMATOID ARTHRITIS - Ortiz-Márquez, F.; Garcia Studer, A.; Montañez-Marín, I.; Ramírez-García, T.; Cabezudo-García, P.; Mena-Vázquez, N. (Annals of the rheumatic diseases, 2023)
BackgroundPatients with rheumatoid arthritis (RA) present cognitive impairment at a frequency of 38% to 71%.ObjectivesTo study whether there is an association between high sustained inflammatory activity and cognitive impairment in RA patients.MethodsDesign and protocol: controlled cross-sectional observational study of a prospective cohort of patients with RA. Cases: patients with RA from a prospective cohort with onset >16 years and who were selected to start first biologic treatment for moderate-high inflammatory activity. Controls: subjects without inflammatory disease, matched for sex and age with cases. All participants performed the same neuropsychological battery. Variables: the main variable was cognitive impairment defined by a score of < 26 points in the Montreal Cognitive Assessment questionnaire (MoCA test). As secondary variables we included the score in each of the items of the MoCA test separately; the direct and inverse digits span; the STROOP test for the assessment of processing speed (STROOP-P), selective attention (STROOP-C) and inhibition (STROOP-PC); and the Hospital Anxiety and Depression Scale (HADS). Other variables included average inflammatory activity by DAS28-ESR since diagnosis, epidemiological characteristics, comorbidities and treatments.ResultsSixty-two subjects were included. The baseline characteristics are shown in Table 1. RA patients presented a higher frequency of cognitive impairment than controls (64.5% vs. 38.7%; p=0.042), as well as lower mean (SD) values on the MoCA test (23.1 [3.8] vs. 25.1 [3.8]; p=0.046). Fewer RA patients compared to controls achieved the memory item (22 [81.5] vs 30 [100.0]; p = 0.014), naming (24 [88.0] vs 30 [100.0]; p = 0.031), and presented lower mean (SD) values in attention (3.5 [1.5] vs 4.4 [1.4]; p = 0.039). Scores for all subtests are shown in Figure 1. Factors that were associated in multivariate analysis with cognitive impairment in the total sample were age (OR [95% CI], 1.171 [1.068-1.284]; p=0.001), RA diagnosis (OR [95% CI], 4.712 [1.069-12.772]; p=0.041) and university studies (OR [95% CI], 0.089 [0.010-0.829]; p=0.034) (R2 = 0.405). The model in RA patients found association of cognitive impairment with age (OR [95% CI], 1.230 [1.020-1.485]; p=0.030), and mean DAS28-ESR (OR [95% CI], 1.704 [1.072-4.003]; p=0.048) (R2 = 0.380). Statistical analysis: descriptive analysis, bivariate analysis between patients and controls, as well as between patients with and without cognitive impairment; and two multivariate logistic regression analyses were performed to analyze the factors associated.ConclusionPatients with RA and high inflammatory activity more frequently presented cognitive impairment compared to the controls. The most affected domains were memory, naming and attention. Factors associated with cognitive impairment were age, educational level and mean DAS28-ESR.Table 1.Baseline characteristics of 31 RA patients and 31 controlsVARIABLERAN= 31CONTROLN = 31P-VALUESex, female, n (%)27 (87.1)27 (87.1)1.000Age years, mean (SD)57.3 (10,6)56.3 (10.9)0.670Academic level0.454Basic schooling, n (%)14 (45.2)15 (48.4)Non-university higher education, n (%)13 (41.9)9 (29.0)University studies, n (%)4 (12.9)7 (22.6)Time since diagnosis of RA, months, median (IQR)79.4 (31.2-191.0)Diagnostic delay, median (RIC), months8.0 (4.0-12.2)Rheumatoid factor >10 U/ml, n (%)27 (87.0)0 (0.0)<0.001ACPA > 20 U//ml, n (%)26 (83.0)0 (0.0)<0.001DAS28-ESR, mean (SD)3,9 (0.8)HAQ, mean (SD)1,1 (0.6)Methotrexate, n (%)22 (71.0)Hydroxychloroquine, n (%)5 (16.1)Leflunomide, n (%)2 (6.5)Sulfasalazine, n (%)2 (6.5)Cognitive impairment (<26 MoCA), n (%)20 (64.5)12 (38.7)0.042Depression (HADS>11), n (%)5 (16.1)1 (3.2)0.086Anxiety (HADS>11), n (%)9 (29.0)5 (16.1)0.224Abbreviation: ACPA: anti-citrullinated C-peptide antibodies; DAS28-ESR: 28-joint Disease Activity Score; ESR: erythrocyte sedimentation rate; HAQ: Health Assessment QuestionnaireFigure 1.Comparison of mean values of cognitive subtests between patients and controlsAcknowledgementsFunding: This work was supported by FIS Grant PI22/01207 (Instituto Carlos III, Fondos FEDER).Disclosure of InterestsNone Declared.